If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x = 12 + -3(x + 1) Reorder the terms: 4x = 12 + -3(1 + x) 4x = 12 + (1 * -3 + x * -3) 4x = 12 + (-3 + -3x) Combine like terms: 12 + -3 = 9 4x = 9 + -3x Solving 4x = 9 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4x + 3x = 9 + -3x + 3x Combine like terms: 4x + 3x = 7x 7x = 9 + -3x + 3x Combine like terms: -3x + 3x = 0 7x = 9 + 0 7x = 9 Divide each side by '7'. x = 1.285714286 Simplifying x = 1.285714286
| (3x^3y^-4/6x^-2y^6)^1 | | 3(1-x)+1=2(-7) | | -7+v=-6 | | 4x+6-6x=3(x+3)-11 | | -8x-4+4x=-9x+2 | | F(x)=-5x^2+2x-3 | | 3m-15=12 | | 122=x^2 | | 7x+19=61 | | 5.3-(3.7)=13.81 | | 1/2(10-2x)=12 | | 7=8r+7r | | 36K=2088 | | N-(-7)=-8 | | 12x=4x+3x+300 | | 2*3-2*4x+7=0 | | 60000=x+(x+15000) | | 33h+1=48 | | 8-a/-7=1 | | 21=10a+1 | | 82=x^2 | | 10=-3a+37 | | 7-n=-8 | | -4x=10x-2 | | 6g+3(-8+3)=1-g | | 2.5d+7.5=2+4.25d | | 25.6=2.8h+6 | | 7x^2-49x+42=0 | | -3y-9y=-8 | | 3x^5-350=-446 | | 80=10v | | -5x-8+6x=-6x-2 |